2015
DOI: 10.3748/wjg.v21.i16.4852
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in serotonin, transient receptor potential channels and protease-activated receptors in rats with irritable bowel syndrome attenuated by Shugan decoction

Abstract: SGD alleviated VHL and attenuated colon motility in IBS, partly by regulating TRPV1, TRPV4, TRPA1, PAR2, 5-HT, CgA and SERT, and reducing CGRP and TNF-α level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 36 publications
0
30
0
Order By: Relevance
“…Chronic WAS is well demonstrated to increase pro‐inflammatory cytokines in both gene and protein level in the GI tract . However, it has not been shown that these cytokines are directly involved in WAS‐induced visceral hypersensitivity so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic WAS is well demonstrated to increase pro‐inflammatory cytokines in both gene and protein level in the GI tract . However, it has not been shown that these cytokines are directly involved in WAS‐induced visceral hypersensitivity so far.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic WAS is well demonstrated to increase proinflammatory cytokines in both gene and protein level in the GI tract. 7,8,34 However, it has not been shown that these cytokines are directly involved in WAS-induced visceral hypersensitivity so far. We believed that this is the first report showing the direct link between the cytokines and chronic WAS-induced visceral hypersensitivity, because anakinra or IL-6 antibody abolished the response.…”
Section: Stress and Visceral Hypersensitivitymentioning
confidence: 99%
“…As an important regulatory monoamine neurotransmitter in the brain-gut axis, 5-HT is widely present in the CNS and gastrointestinal tract where 95% of 5-HT is stored in enterochromaffin (EC) cells of the intestinal mucosa. Various stimuli such as elevated pressure in the intestinal lumen, allergic reactions, and acetylcholine can stimulate ECs to release 5-HT to signal the nervous and endocrine systems to produce visceral hypersensitivity, pain, and stool changes [ 17 – 19 ]. Studies suggest that, in IBS patients, an abnormal increase of 5-HT in the colon mucosa and serum is associated with visceral hypersensitivity [ 20 – 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study performed by Pan et al [ 10 ] showed that TXYF could significantly relieve the abdominal pain/discomfort and improved the stool property in D-IBS patients. A recent animal experiment also demonstrated that TXYF could increase the pain threshold and decrease the number of fecal pellets in IBS rats [ 28 ]. However, the curative mechanism has not been clear although much work has been done.…”
Section: Discussionmentioning
confidence: 99%